The Ethylene Biosynthesis Gene CpACO1A: A New Player in the Regulation of Sex Determination and Female Flower Development in Cucurbita pepo - Cebrián, Gustavo; Iglesias-Moya, Jessica; Romero, Jonathan; Martínez, Cecilia; Garrido, Dolores; Jamilena, Manuel (Frontiers in Plant Science, 2022)
A methanesulfonate-generated mutant has been identified in Cucurbita pepo that disrupts sex determination. The mutation converts female into hermaphrodite flowers and disrupts the growth rate and maturation of petals and carpels, delaying female flower opening, and promoting the growth rate of ovaries and the parthenocarpic development of the fruit. Whole-genome resequencing allowed identification of the causal mutation of the phenotypes as a missense mutation in the coding region of CpACO1A, which encodes for a type I ACO enzyme that shares a high identity with C. sativus CsACO3 and C. melo CmACO1. The so-called aco1a reduced ACO1 activity and ethylene production in the different organs where the gene is expressed, and reduced ethylene sensitivity in flowers. Other sex-determining genes, such as CpACO2B, CpACS11A and CpACS27A, were differentially expressed in the mutant, indicating that ethylene provided by CpACO1A but also the transcriptional regulation of CpACO1A, CpACO2B, CpACS11A, and CpACS27A are responsible for determining the fate of the floral meristem towards a female flower, promoting the development of carpels and arresting the development of stamens. The positive regulation of ethylene on petal maturation and flower opening can be mediated by inducing the biosynthesis of JA, while its negative control on ovary growth and fruit set could be mediated by its repressive effect on IAA biosynthesis.